2011
DOI: 10.1021/ol201448h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Counterion Structure on Rates and Diastereoselectivities in α,β-Unsaturated Iminium-Ion Diels–Alder Reactions

Abstract: The use of cyclic α,β-unsaturated iminium-ion dienophiles is documented in two highly diastereoselective Diels-Alder (DA) reactions. The dienophilic counterion was found to have a significant effect on reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Following these studies, in 2011, advances in intermolecular Diels-Alder reactions of iminium ions were reported by Evans and co-workers (Scheme 5). 44 Remarkably, sev-en-and six-membered NH-,-unsaturated iminium salts 27 and 28 were found to be isolable and stable to flash column chromatography. Iminium ions 27 and 28 were used in Diels-Alder reactions with simple dienes 29, with spirocyclic adducts 30 and 31 afforded in excellent yields and high endo selectivities (>90:10) due to LUMO-lowering activation of the iminium dienophiles.…”
Section: Use Of More Stable Iminium Ion Dienophiles For Diels-alder Reactionsmentioning
confidence: 96%
See 1 more Smart Citation
“…Following these studies, in 2011, advances in intermolecular Diels-Alder reactions of iminium ions were reported by Evans and co-workers (Scheme 5). 44 Remarkably, sev-en-and six-membered NH-,-unsaturated iminium salts 27 and 28 were found to be isolable and stable to flash column chromatography. Iminium ions 27 and 28 were used in Diels-Alder reactions with simple dienes 29, with spirocyclic adducts 30 and 31 afforded in excellent yields and high endo selectivities (>90:10) due to LUMO-lowering activation of the iminium dienophiles.…”
Section: Use Of More Stable Iminium Ion Dienophiles For Diels-alder Reactionsmentioning
confidence: 96%
“…Scheme 5 Iminium ion Diels-Alder cycloadditions by Evans et al 44 Evans' work therefore prompted a redesign of our iminium ion dienophile scaffold to incorporate a methyl substituent at the imine center (Scheme 6, A), which would serve…”
Section: Use Of More Stable Iminium Ion Dienophiles For Diels-alder Reactionsmentioning
confidence: 99%
“…39 We found that exposure of the TFA salts 30 or 31 to 1 equiv of methanesulfonic acid at 55 °C induced counterion metathesis and efficient intramolecular cycloaddition. Monitoring the reactions by 1H NMR spectroscopy over 5 days allowed us to observe the formation of himandravine-type cycloadducts 32 or 33 , along with GB17-type cycloadducts 34 or 35 that underwent complete isomerization to the conjugated iminium ions 36 or 37 in situ.…”
Section: Resultsmentioning
confidence: 82%
“…Future computational work will be focused on the study of other factors influencing the interconversion of aminoketone and imine forms of PnTX A, e.g., the presence of two bridging water molecules to facilitate the proton transfer and the protonation state of the nitrogen atom (imine vs iminium), as well as the potential of the biomimetic Diels–Alder reaction to assemble the macrocyclic framework of pinnatoxins. 12 …”
Section: Discussionmentioning
confidence: 99%